Policy translation: a reply. Issue 1 (2nd January 2016) - Spicker, Paul
Abstract : This is a reply to: Balen, M. E. and C. Leyton. 2016. "Policy translation: an invitation to re-visit the work of Latour, Star and Marres." Global Discourse 6 (1–2): 101–115.http://dx.doi.org/10.1080/23269995.2014.1000571 .